Investigation of Potential Waste Insulating Material Properties with Different Heat Transfer Fluid for Thermal Storage Application - Tanti Zanariah, Shamshir Ali; R. A., Bakar; Gan, Leong Ming; Billy, Anak Sup; Mohd Farid, Zainudin (2013)

(untitled)
Though thermal energy storage (TES) is well developed hugely in most of the solar power generation plant, it is less growth in implementing a modular type of TES in a solar plant, e.g. Solar dish/Stirling engine application. The main issue in designing the TES system is its thermal capacity of storage materials, e.g. insulator. This study is focusing on the potential waste material as an insulator for thermal energy storage applications. The insulator usage is to reduce the heat transfer between two medium and the capability is measured by its resistance to heat flow. It is needed to obtain optimal material to energy conversion at the same time reduce the waste generation. Therefore, a small-scale experimental testing of natural cooling process of an insulated tank within a confined room without any forced cooling system, e.g. fan. The testing is repeated by changing the insulator using the potential waste material from natural and industrial waste and also by changing the heat transfer fluid (HTF). The analysis is performed on the relationship between heat loss and the reserved period by the insulator. The results indicate the percentage of period of the insulated tank withstands the heat compared to non-insulated tank, e.g. foam reserved the period of 333% more than non-insulated tank to withstand the heat transfer of cooking oil to the surrounding. The paper finally justifies the most potential waste material as an insulator in different heat transfer fluid.